Development of a Machine Vision System for Solar Wafer Counting - Nan Wang; Shuguang Zhang; Man Cheng; Zhenjiang Cai (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The traditional manual counting wafers leaded to the silicon wafer cracked by operating frequently. Instead of the manual work, this paper proposed a system to counting wafers based on Machine Vision theory and Image Processing algorithm. We designed a counter system and adopted infrared led as parallel illumination source. In image pre-processing, this paper presented a series of algorithms, which contained image smoothing, uneven image correction and image morphology operation. This paper proposed a vertical projection counting based on statistics analysis substitute for the Hough straight lines detection, and the method had been achieved ideal effects by experimental results. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5108